GENERALIZED VARIATIONAL-LIKE INCLUSION PROBLEM INVOLVING (H(.,.),)-MONOTONE OPERATORS IN BANACH SPACES - Bhat, M. I.; Zahoor, B. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this paper, we consider the generalized variational-like inclusion problem involving (H(.,.),η)-monotone operators in Banach spaces. Using proximal operator technique, we prove the existence of solution and suggest an iterative algorithm for solving the generalized variational-like inclusion problem. Also, we discuss the convergence analysis of the iterative algorithm. The results presented in this paper improve and generalize many known results in the literature.